2004
DOI: 10.1038/sj.ijo.0802554
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of insulin signaling and adipogenesis by rapamycin: effect on phosphorylation of p70 S6 kinase vs eIF4E-BP1

Abstract: OBJECTIVE: Insulin-responsive adipogenic signaling molecules include insulin receptor substrates (IRS)-1 and -2, phosphoinositide 3-kinase (PI3K), and protein kinase B (PKB; also known as Akt). Mammalian target of rapamycin (mTOR) is a PKB substrate, and regulates p70 S6 kinase (p70 S6K). Since p70 S6K is an insulin-responsive kinase downstream of PI3K and PKB, its potential role in adipogenic insulin signaling was investigated. DESIGN: We measured the effect of rapamycin, a specific inhibitor of mTOR, on insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 36 publications
3
43
0
2
Order By: Relevance
“…In an early experiment, it was shown that the addition of rapamycin to the differentiation mixture impairs adipogenesis in mouse and human mesenchymal stem cells (18). In fact, rapamycin inhibits the activity and expression of transcription factor peroxisome proliferator-activated receptor γ (PPARγ) (19), which is the master regulator of adipogenesis. The central importance of mTORC1 in the signaling network of adipocyte stem cell differentiation was fueled by the accumulating knowledge that mTORC1 integrates and transduces signals regulating energy balance (20).…”
mentioning
confidence: 99%
“…In an early experiment, it was shown that the addition of rapamycin to the differentiation mixture impairs adipogenesis in mouse and human mesenchymal stem cells (18). In fact, rapamycin inhibits the activity and expression of transcription factor peroxisome proliferator-activated receptor γ (PPARγ) (19), which is the master regulator of adipogenesis. The central importance of mTORC1 in the signaling network of adipocyte stem cell differentiation was fueled by the accumulating knowledge that mTORC1 integrates and transduces signals regulating energy balance (20).…”
mentioning
confidence: 99%
“…Acivation of p70S6K1 p70S6 protein kinase is an insulin-sensitive serin/threonin kinase, located downstream to protein kinase B (PKB), although indirectly as PKB substrate. PKB may phosphorylate mTORC1, and then mTORC1 regulated p70S6K activity [6]. mTORC1 phosphorylated p70S6K1 on Thr 389, allowing phosphoinositide-dependent protein kinase 1 (PDK1) bound and phosphorylated S6K1 on Thr229, therefore, it fully activated S6K1.…”
Section: Discussionmentioning
confidence: 99%
“…In preadipocyte, expression of C/EBPβ dan C/EBPδ is upregulated by the activation of prostacyclin receptor which induces the binding of CREB and/or ATF-1 (activation transcription factor 1) to C/EBP promoter [5]. De Groot et al in El-Charr et al [6] reported that CREB was regulated by p70S6K. However, there has been no studies which evaluate the mTORC1  p70S6K1  CREB  CEBPδ pathway extensively.…”
Section: Introductionmentioning
confidence: 99%
“…PPARγ yang merupakan regulator utama adipogenesis Selain itu, meskipun homeostasis energi tubuh secara (17,18). keseluruhan dipelihara oleh berbagai jalur, kebanyakan…”
Section: Pendahuluanunclassified
“…PKB dapat memfosforilasi sering pula disebut signal transduction and transcription mTORC1 dan kemudian mTORC1 meregulasi aktivitas protein meregulasi berbagai aspek pada proses seluler p70S6K (17 korelasi positif antara aktivitas GPDH dan asam lemak seluler terutama MUFA C16:1 dan C18:1 (28). Pada penelitian ini kelompok yang diberi kombinasi rapamycin dan inhibitor STAT3 menunjukkan aktivasi Pada penelitian ini, oleh karena terjadi penghambatan STAT3 yang paling rendah dibandingkan dengan yang pada jalur upstream dari proses adipogenesis yaitu dengan hanya diberi inhibitor STAT3 saja atau rapamycin saja.…”
Section: Aktivitas Enzim Glisero-3-fosfodehidrogenase (Gpdh)unclassified